Assessing the degree of industrialisation in construction – a case of Uganda - Alinaitwe, Henry Mwanaki; Mwakali, Jackson; Hansson, Bengt (Journal of Civil Engineering and Management, 2006)
Industrialisation is seen as one of the philosophies that can be employed to be able to increase the productivity of the construction industry. There are many forms and classifications of industrialisation and these have to be put in the context while seeking improvement of productivity by industrialisation. A systems approach is used to analyse the players and factors for industrialisation of the construction sector. Case studies were used to study industrialisation in the construction sector in a developing country. Performance metrics are suggested and used to measure the extent of industrialization in Uganda. It is concluded that the level of industrialisation in Uganda seems to be low. However, there is a need for a wider comparison in order to come up with generic indicators. Ugandos statybos industrializacijos laipsnio įvertinimas Santrauka. Industrializacija yra reiškinys, kuris gali padėti didinti statybos pramonės našumą. Produktyvumui gerinti gali būti pritaikyta daug industrializacijos formų. Statybos sektoriaus industrializavimo dalyviams ir veiksniams analizuoti naudojamas sisteminis požiūris. Konkrečiais pavyzdžiais apibūdinama besivystančios šalies statybos sektoriaus industrializacija. Pasiūlyta ir panaudota Ugandos statybos industrializacijos masto matavimo sistema. Daroma išvada, jog Ugandos industrializacijos lygis yra per menkas. Vis dėlto, norint apibendrinti, reikia išsamesnių tyrimų. Raktiniai žodžiai: industrializacija, matavimo sistema, statyba, sisteminė analizė, našumas, besivystančios šalys. First Published Online: 14 Oct 2010